Energy and Sustainability V 2014
DOI: 10.2495/esus140031
|View full text |Cite
|
Sign up to set email alerts
|

A framework to evaluate the energy efficiency potential of Kuwaiti homes

Abstract: Energy demand and consumption rates in Kuwait are amongst the highest in the world. This is largely due to a substantial amount of waste and overconsumption of energy in the residential building sector which accounts for almost 60% of Kuwait's national electrical power generated. In spite of the existence of an Energy Conservation Code of Practice for Buildings, homes in Kuwait continue to be designed and built with little consideration to their climate, consuming significant amounts of electricity. There is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, in a survey reported by Jaffar et al [25], covering 170,815 apartments in Kuwait, it was found that the average annual electrical energy consumption for all purposes per square meter equates to 127 kWh/m 2 . Assuming that 70% of this energy is utilized for space cooling [4], this results in 88 kWh/m 2 .…”
Section: Temperature Level Control (Tlc) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a survey reported by Jaffar et al [25], covering 170,815 apartments in Kuwait, it was found that the average annual electrical energy consumption for all purposes per square meter equates to 127 kWh/m 2 . Assuming that 70% of this energy is utilized for space cooling [4], this results in 88 kWh/m 2 .…”
Section: Temperature Level Control (Tlc) Modelmentioning
confidence: 99%
“…Our study indicates that the peak cooling load resulting from simulating the top-floor apartment amounted to a power density of 45 W/m 2 , which falls below the maximum limit set by the Ministry of Electricity and Water (MEW). Furthermore, in a survey reported by Jaffar et al [25], covering 170,815 apartments in Kuwait, it was found that the average annual electrical energy consumption for all purposes per square meter equates to 127 kWh/m 2 . Assuming that 70% of this energy is utilized for space cooling [4], this results in 88 kWh/m 2 .…”
Section: Temperature Level Control (Tlc) Modelmentioning
confidence: 99%